2020
DOI: 10.1126/science.aay4919
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of second-generation HIV integrase inhibitor action and viral resistance

Abstract: Although second-generation HIV integrase strand-transfer inhibitors (INSTIs) are prescribed throughout the world, the mechanistic basis for the superiority of these drugs is poorly understood. We used single-particle cryo–electron microscopy to visualize the mode of action of the advanced INSTIs dolutegravir and bictegravir at near-atomic resolution. Glutamine-148→histidine (Q148H) and glycine-140→serine (G140S) amino acid substitutions in integrase that result in clinical INSTI failure perturb optimal magnesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
203
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(214 citation statements)
references
References 64 publications
11
203
0
Order By: Relevance
“…In IN GSH, the N-terminal amino group is oriented toward the C-terminal end of the ɑ2 helix, whereas in IN 1F, it is flipped ~ 180° and oriented toward the ɑ3 helix of a neighboring NTD. The same NTD–NTD interface is observed in dodecameric HIV-1, hexadecameric MVV, and SIV intasome structures [ 22 25 ], and the NTDs modeled at this position adopt extended ɑ1 helical structures in four of six structures (Additional file 3 : Figure S3). The NTDs that do not form an NTD–NTD interface show a variety of structures: disordered, partially unstructured, and extended (Additional file 3 : Figure S3).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…In IN GSH, the N-terminal amino group is oriented toward the C-terminal end of the ɑ2 helix, whereas in IN 1F, it is flipped ~ 180° and oriented toward the ɑ3 helix of a neighboring NTD. The same NTD–NTD interface is observed in dodecameric HIV-1, hexadecameric MVV, and SIV intasome structures [ 22 25 ], and the NTDs modeled at this position adopt extended ɑ1 helical structures in four of six structures (Additional file 3 : Figure S3). The NTDs that do not form an NTD–NTD interface show a variety of structures: disordered, partially unstructured, and extended (Additional file 3 : Figure S3).…”
Section: Resultsmentioning
confidence: 61%
“…This NTD does not form NTD-NTD interactions in dodecameric or hexadecameric intasomes and shows a range of ɑ1 helical structures: disordered, partially unstructured, and extended [23]. Intasomes of a closely-related simian immunodeficiency virus were prepared with IN purified with an N-terminal affinity tag and subsequent human rhinovirus 3C protease cleavage, leaving 3 residues (G-P-G-) preceding F1 [22]. The NTDs in these structures show extended ɑ1 helices.…”
Section: H12cmentioning
confidence: 99%
See 1 more Smart Citation
“…And Bictegravir and Dolutegravir are integrase inhibitors used in combination with other drug for treatment of HIV infection. They are structurally related as the former is a derivation from the latter (75). And their binding energies to nsp5 are also very similar (-9.5 kcal/mol for Bictegravir and -8.9…”
Section: Drug Perform Well In Our Screening But Not Under Clinical Trialmentioning
confidence: 87%
“…Recent cryo-EM studies have revealed how these compounds, as well as other related molecules, are bound to integrase ( Fig. 4 J) [98] , [99] , coordinating two Mg 2+ ions in the active site. The structure of a resistant mutant in complex with bictegravir provides insights into the mechanism of resistance.…”
mentioning
confidence: 99%